Genetic analysis of a diallel cross in tomato II. Vegetative characters - Miranda, João Eustáquio Cabral de; Maluf, Wilson Roberto; Campos, Joenes Pelúzio de (Pesquisa Agropecuaria Brasileira, 2014)
Jinks-Hayman genetic analysis was performed on vegetative characteres of tomato (Lycopersicon esculentum Mill.) plants in a diallel cross of six cultivars - Kada, Santo Antônio, São Sebastião, Ângela, Floradel e BGH 3470. The six cultivars and their fifteen possible F1 hybrids were tested in 1977 in two locations: Viçosa (MG) and Ponte Nova (MG). There was no evidence of epistasis or overdominance in any of the characters studied. There was complete dominance in the direction of more clusters per plant, longer plants and higher number of internodes per plant, and incomplete dominance for higher number of fruits per cluster and lower number of locules per fruit.